2009
DOI: 10.1017/s0022215109004812
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fixation suppression is a risk factor for vertigo after cochlear implantation

Abstract: Pre-operative impaired visual fixation suppression is a major risk factor for the occurrence of vertigo after cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Central vestibular compensatory mechanisms may suppress peripheral vestibular dysfunctions. In CI patients with conserved ability of visual fixation suppression, vertigo symptoms were found significantly less often 17 . The poor correlation between the patients' subjective complaints and the objectively measurable changes in neurotologic tests may be explained by the wide array of possible causes of balance disorders after CI.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Central vestibular compensatory mechanisms may suppress peripheral vestibular dysfunctions. In CI patients with conserved ability of visual fixation suppression, vertigo symptoms were found significantly less often 17 . The poor correlation between the patients' subjective complaints and the objectively measurable changes in neurotologic tests may be explained by the wide array of possible causes of balance disorders after CI.…”
Section: Discussionmentioning
confidence: 94%
“…In CI patients with conserved ability of visual fixation suppression, vertigo symptoms were found significantly less often. 17 The poor correlation between the patients' subjective complaints and the objectively measurable changes in neurotologic tests may be explained by the wide array of possible causes of balance disorders after CI. Benign paroxysmal positioning vertigo, Tullio phenomenon, electric stimulation, or psychosomatic causes cannot be quantified by caloric testing, rotatory chair testing, or VEMP testing.…”
Section: Discussionmentioning
confidence: 99%
“…Patients of studies undergoing the RW approach do not have significantly increased vertigo after cochlear implantation, in contrast to studies including patients undergoing cochleostomy. Postoperative vertigo (new onset and perioperatively unchanged vertigo) occurred in 8.8% (532 of 6,120 patients) after cochleostomy and in 5.5% (48 of 868) after RW approach . Patients undergoing RW approach have a significantly lower risk of postoperative vertigo compared with cochleostomy (OR of 0.61; 95% CI 0.45–0.83; P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This timing of postoperative assessment varies between studies and could influence test results (Abouzayd et al 2017), although the present study showed that in general the length of the postoperative follow up interval was not correlated with any vestibular outcome. The evolution of vestibular symptoms over time may indicate a central compensatory effect (Kubo et al 2001;Buchman et al 2004;Filipo et al 2006;Krause et al 2009). The present findings of a clinically non-significant effect on DHI score might therefore possibly be influenced by the time of assessment.…”
Section: Discussionmentioning
confidence: 99%